2005
DOI: 10.1038/sj.gene.6364178
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of the 1858C>T polymorphism in the PTPN22 gene in juvenile idiopathic arthritis and other autoimmune diseases

Abstract: A functional single nucleotide polymorphism, 1858C4T, in the PTPN22 gene, encoding a tyrosine phosphatase, has been reported to be associated with type I diabetes and some other autoimmune diseases. To further investigate whether this polymorphism may be a general susceptibility factor for autoimmunity, we performed an association study in five different autoimmune diseases, three previously not tested. We found an association with juvenile idiopathic arthritis (OR ¼ 1.41; P ¼ 0.04), not previously reported, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
97
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(105 citation statements)
references
References 19 publications
5
97
0
3
Order By: Relevance
“…The few positive reports of an association with RF Ϫ RA, in view of the vast majority of negative reports, might be false positives, as suggested by the clear negative linkage findings in our study (13). There were association reports for one form of idiopathic juvenile arthritis, but a well powered negative linkage study raised serious doubts on the reality of the association (28,(34)(35)(36).…”
Section: Discussionmentioning
confidence: 48%
“…The few positive reports of an association with RF Ϫ RA, in view of the vast majority of negative reports, might be false positives, as suggested by the clear negative linkage findings in our study (13). There were association reports for one form of idiopathic juvenile arthritis, but a well powered negative linkage study raised serious doubts on the reality of the association (28,(34)(35)(36).…”
Section: Discussionmentioning
confidence: 48%
“…These JIA results do not support the findings of a previous study, which suggested that the PTPN22 1858T allele variant is associated with this disease. 9 However, the relatively small sample size (230 probands in the current study) does not preclude a modest effect from this gene in Finnish JIA. Differences in results between the current study and the previous study performed in Norwegian subjects may also be explained by differences between populations or the possibility of hidden population structure that was not controlled for in the previous study.…”
mentioning
confidence: 71%
“…The identification of PTPN22 1858 C/T as a putative disease risk allele in type 1 diabetes (T1D) [1][2][3][4][5][6] and subsequently RA [7][8][9] and other autoimmune diseases including SLE, 10,11 Graves disease 12 and JIA 9 has engendered considerable excitement. 13 PTPN22 also known as LYP (lymphocyte phosphatase) encodes a hematopoietic tissue-specific protein tyrosine phosphatase that is thought to inhibit T-cell activation through its association with the Csk tyrosine kinase.…”
mentioning
confidence: 99%
“…Finally, since a single-nucleotide polymorphism in position 1858 in PTPN22 (that encodes LYP) has been found to predispose carriers to multiple autoimmune diseases (Bottini et al, 2004;Smyth et al, 2004;Begovich et al, 2004;Viken et al, 2005;Kyogoku et al, 2004;Vang et al, 2005;reviewed in Bottini et al, 2006), it seems quite possible that similar variants of PTP-PEST may be involved in immunological disease (Mustelin, 2006). It is therefore important to clarify the regulation and physiological functions of these phosphatases in T lymphocytes and other immune cells.…”
Section: Discussionmentioning
confidence: 99%